Effects of boundary and bulk control technology in cholesteric liquid crystals. (2nd July 2016) - Kim, Gi Heon; Lee, Won-Jae; Kim, Han Na; Kim, Yong-Hae
ABSTRACT: We fabricate a cholesteric liquid crystal display (Ch-LCD) having high reflectance and fast response time by doping R-811 into a nematic LC. The field-on and the field-off response times are 39 and 15 ms, respectively. The helical pitch is governed by R-811 that induced the cholesteric color. The boundary and bulk condition are strong effect on changes in the electro-optic behavior. The boundary condition controlled by rubbing strength has strong effects on the field-off response time and the reflectance variation. The bulk condition controlled by cell gap and R-811 concentration induced significant changes on operating voltage and threshold voltage.